The Children Return : a Bruno, Chief of Police novel - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series., 2015)
"When an undercover agent tracking domestic jihadists is found murdered, it's troubling enough for Bruno's beloved village. But when this is followed by the return of Sami, a local autistic youth thought lost to Islamic extremism, provincial St. Denis suddenly becomes a front line in the global war on terror."